(untitled) (Konturen, 2013)
“The Impossibility of the Wenderoman” argues against the conventional conception of the Wenderoman (and of thematically related films and plays) that views it essentially as a kind of cultural document of the German “Wende.” Placing the question within the larger problematic of historical fiction and political literature, this paper notes first that the very genre is itself an impossibility insofar as its boundaries are ever-expanding. The quintessential contribution of the genre, this paper argues, is twofold: retrospective and “conciliatory.” It is the first insofar as we are willing to look beyond literature and film that focuses principally on the Wende per se, and instead take Unification as a juncture from which truly to look back (taking advantage of the new temporal perspective given us by “the turn”), and thus reevaluate Cold War conventions, specifically those governing German-German and German-American cultural relations that often went unquestioned in the postwar period. In other words, the Wenderoman dimension I elaborate (drawing especially on Kempowski’s Letzte Gruesse) may contribute to a more profound understanding of the period it “closes” than the one it ostensibly celebrates and inaugurates. Secondly, the Wenderoman functions as a prominent vehicle of cultural memory, preserving various moments of a Marxist-inspired social agenda for future generations. Agamben’s notion of “the contemporary” as well as foundational concepts of “cultural memory” are useful here. The discussion features well-known films (Good Bye, Lenin! and Das Leben der Anderen), theater (Brussig’s Leben bis Maenner), as well as several novels. Whether this process of cultural “sifting” will remain purely elegiac, or serve as a resource for imagining alternative social possibilities in the future is of course impossible to know—both because it is far too general of a hypothesis, and still far too early to tell.